Mathematical problem solving of elementary students based on adversity quotient - Siti Munawwarah; Aprilia Tina Lidyasari; Verawati Munafiroh (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
This study investigates fifth-grade students’ mathematical problem-solving abilities based on their Adversity Quotient (AQ) types and identifies error patterns across Polya’s problem-solving stages. Employing a descriptive qualitative design, the research was conducted at Keputran 2 Elementary School, Yogyakarta, involving 24 purposively selected students. Data were obtained through the Adversity Response Profile (ARP) questionnaire and a mathematical problem-solving test. The AQ results categorized students into four climbers, seven campers, and thirteen quitters. One student from each AQ type was further analyzed through their written responses. Findings revealed that climber-type students successfully completed all stages of Polya’s framework, demonstrating perseverance and accuracy yet showing limited reflective evaluation. Camper-type students completed all stages inconsistently, particularly in verifying their results. Quitter-type students were unable to complete the stages, displaying conceptual and procedural misconceptions. The study concludes that differentiated instructional strategies are essential: quitters benefit from contextualized tasks and extrinsic motivation; campers require scaffolded feedback; and climbers need challenging problems to foster deeper reflection. These insights emphasize the pedagogical importance of integrating AQ-based differentiation to enhance mathematical problem-solving competence among elementary students.